A Randomized Comparison of Plasma Levobupivacaine Concentrations Following Thoracic Epidural Analgesia and Subpleural Paravertebral Analgesia in Open Thoracic Surgery - Matek, Jan; Cernohorsky, Stanislav; Trca, Stanislav; Krska, Zdenek; Hoskovec, David; Bruthans, Jan; Sima, Martin; Michalek, Pavel (Journal of clinical medicine, 2020)
BACKGROUND: The aim of this study was to compare plasma levobupivacaine concentrations in thoracic epidural and subpleural paravertebral analgesia. METHODS: Forty-four patients indicated for open lung resection had an epidural catheter inserted preoperatively or a subpleural catheter surgically. A bolus of 0.25% levobupivacaine at a dosage of 0.5 mg × kg-1 was given after the thoracotomy closure. Plasma levobupivacaine level at 30 min was the primary outcome. Pharmacokinetic modeling was performed subsequently. Secondary outcomes included the quality of analgesia, complications, and patients'mobility. RESULTS: Plasma concentrations were similar 30 min after application-0.389 mg × L-1 in the epidural and 0.318 mg × L-1 in the subpleural group (p = 0.33) and lower in the subpleural group at 120 min (p = 0.03). The areas under the curve but not maximum concentrations were lower in the subpleural group. The time to reach maximum plasma level was similar in both groups-27.6 vs. 24.2 min. No clinical symptoms of local anesthetic toxicity were recorded. CONCLUSIONS: Levobupivacaine systemic concentrations were low in both groups without the symptoms of toxicity. This dosage should be safe for postoperative analgesia after thoracotomy.
Keywords: thoracotomy; levobupivacaine; subpleural catheter; toxicity; epidural analgesia